2015
DOI: 10.3847/0004-637x/816/1/43
|View full text |Cite
|
Sign up to set email alerts
|

The Criterion of Supernova Explosion Revisited: The Mass Accretion History

Abstract: By performing neutrino-radiation hydrodynamic simulations in spherical symmetry (1D) and axial symmetry (2D) with different progenitor models by Woosley & Heger from 12 to 100 M e , we find that all 1D runs fail to produce an explosion and several 2D runs succeed. The difference in the shock evolutions for different progenitors can be interpreted by the difference in their mass accretion histories, which are in turn determined by the density structures of progenitors. The mass accretion history has two phases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 77 publications
5
76
0
Order By: Relevance
“…Many studies of the explosion mechanism of CCSNe (e.g. Murphy & Burrows 2008;Nordhaus et al 2010;Hanke et al 2012;Janka 2012;Suwa et al 2016) found a positive correlation between the neutrino luminosity of a core and its tendency towards explosion with shock revival setting in if a critical luminosity that depends on, among other factors, the mass accretion rate of the core, is exceeded. The similar times of explosion found in model 35OC-Rw and model 35OC-Sw seem to contradict this connection.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies of the explosion mechanism of CCSNe (e.g. Murphy & Burrows 2008;Nordhaus et al 2010;Hanke et al 2012;Janka 2012;Suwa et al 2016) found a positive correlation between the neutrino luminosity of a core and its tendency towards explosion with shock revival setting in if a critical luminosity that depends on, among other factors, the mass accretion rate of the core, is exceeded. The similar times of explosion found in model 35OC-Rw and model 35OC-Sw seem to contradict this connection.…”
Section: Resultsmentioning
confidence: 99%
“…For more massive progenitors with iron core, multi-dimensional (multi-D) effects such as neutrino-driven convection (e.g., Bethe 1990;Herant et al 1994;Burrows et al 1995;Janka & Müller 1996;Müller & Janka 1997) and the standing-accretion-shock-instability (SASI, Blondin et al 2003;Foglizzo et al 2006;Foglizzo et al 2007;Ohnishi et al 2006;Blondin & Mezzacappa 2007;Iwakami et al 2008;Iwakami et al 2009;Fernández & Thompson 2009;Hanke et al 2012; 2012; Couch 2013;Fernández et al 2014, see Foglizzo et al 2015 for a review) have been suggested to help the onset of the neutrino-driven explosion. Recently this has been confirmed by a number of self-consistent two-(2D) and three-dimensional (3D) simulations (e.g., Buras et al 2006;Ott et al 2008;Marek & Janka 2009;Bruenn et al 2013;Suwa et al 2010;Suwa et al 2014;Müller et al 2012a;Müller et al 2013;Takiwaki et al 2012;Takiwaki et al 2014;Hanke et al 2013;Dolence et al 2014;Bruenn et al 2014;Müller & Janka 2014, see Mezzacappa et al 2015Burrows 2013;Kotake et al 2012 for recent review)). Up to now, the number of these stateof-the-art models amounts to ∼ 40 covering the zero-age main sequence (ZAMS) mass from 8.1 M ⊙ (Müller et al 2012a) to 27 M ⊙ …”
Section: Introductionmentioning
confidence: 83%
“…Recent multi-dimensional simulations of neutrino radiation hydrodynamics have shown diversity of numerical results (e.g. Bruenn et al 2013;Suwa et al 2014;Dolence et al 2015;Melson et al 2015b, used the same progenitor models and obtained different results). In addition, most exploding simulations exhibited order of magnitude smaller explosion energy than observation and remnant compact objects often gained mass above the maximum mass of a NS, which would collapse to BHs instead of NSs.…”
Section: Methodsmentioning
confidence: 99%
“…For the hydrodynamics simulations, we employ a twodimensional (2D) neutrino-radiation hydrodynamics code, which is developed and used for investigating SN explosion mechanism (Suwa et al 2010(Suwa et al , 2011(Suwa et al , 2013Suwa et al 2014;Suwa 2014). With ZEUS-2D code (Stone & Norman 1992) as a base for the solver of hydrodynamics, we employ an equation of state of Lattimer & Swesty (1991) with an incompressibility K = 220 MeV and solve the spectral transfer of neutrinos by the isotropic diffusion source approximation (IDSA) scheme (Liebendörfer et al 2009) that splits the neutrino distribution function into two components, both of which are solved by using separate numerical techniques.…”
Section: Methodsmentioning
confidence: 99%